Padrões sinóticos associados a casos extremos de precipitação no Estado de São Paulo - Munhoz, Júlia Crepaldi [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
In this work, a study was made of the days in which precipitation events exceeded the 99% percentile in the state of São Paulo (SP), based on data from the automatic stations of the Instituto Nacional de Meteorologia (INMET), between the period from January to from 2010 to December 2019. The synoptic situations were analyzed through the pressure fields at mean sea level (PNMM), dynamic and thermodynamic fields for the day of the event. To obtain the PNMM standards on the day of the event, the Principal Component Analysis (PCA) methodology was used. The results show the circulation patterns associated with the occurrence of extreme precipitation events for the state of São Paulo, which represent approximately 74% of the cases selected in this study. The first dominant synoptic pattern shows a stationary frontal system over the state of São Paulo, the second pattern that encompasses several cases is a Convergence Zone, the third PNMM pattern is the result of a confluence of winds from a low east of the Andes and the counterclockwise circulation of the Subtropical South Atlantic High (ASAS) that carries moisture to the state of SP and the fourth pattern acquired is the result of moisture brought from the Amazon and a passing cold front.

Neste trabalho foi feito um estudo dos dias em que os eventos de precipitação excederam o percentil de 99% no estado de São Paulo (SP), embasado nos dados das estações automáticas do Instituto Nacional de Meteorologia (INMET), entre o período de janeiro de 2010 à dezembro de 2019. Foram analisadas as situações sinóticas através dos campos de pressão ao nível médio do mar (PNMM), campos dinâmicos e termodinâmicos para o dia do evento. Para a obtenção dos padrões da PNMM no dia do evento, foi utilizada a metodologia de Análise de Componentes Principais (ACP). Os resultados mostram os padrões de circulação associados à ocorrência dos eventos extremos de precipitação para o estado de São Paulo que representam aproximadamente 74% dos casos selecionados neste estudo. O primeiro padrão sinótico dominante mostra um sistema frontal estacionário sobre o estado de São Paulo, o segundo padrão que engloba vários casos é uma Zona de Convergência, o terceiro padrão de PNMM é resultante de uma confluência de ventos de uma baixa ao leste dos Andes e a circulação anti-horária da Alta Subtropical do Atlântico Sul (ASAS) que carrega umidade para o estado de SP e o quarto padrão adquirido é resultante da umidade trazida da Amazônia e de uma frente fria passageira.
Synoptic patterns associated with extreme cases of precipitation in the State of São Paulo
Keywords: Synoptic classification; Principal components; Rainy extremes; Classificação sinótica; Componentes principais; Extremos chuvosos; Chuvas; Precipitação (Meteorologia)